Addressing Student Writing Challenges: A Review of Difficulties and Effective Strategies - Patty, Jusak (LPPM Universitas PGRI Argopuro Jember, 2024)
This narrative literature review examines students' writing challenges and practical strategies to address them. The study synthesizes research on cognitive, linguistic, and affective factors contributing to writing problems, including working memory capacity, vocabulary knowledge, syntactic complexity, writing anxiety, and self-efficacy. The review identifies several promising strategies to support writing development: strategy instruction, collaborative writing, technology-enhanced writing instruction, targeted vocabulary instruction, and individualized feedback. Findings suggest that a multifaceted approach addressing various aspects of writing difficulties is most effective. The study highlights the need for further research on the long-term effectiveness of interventions, the potential of emerging technologies in writing instruction, and culturally responsive approaches to meet diverse student needs.